Field traffic-induced soil compaction under moderate machine-field conditions affects soil properties and maize yield on sandy loam soil - Nawaz, Muhammad Mohsin; Noor, Mehmood Ali; Latifmanesh, Hojatollah; Wang, Xinbing; Ma, Wei; Zhang, Weijian (Frontiers in Plant Science, 2023)
Soil compaction due to field trafficking involves a complex interplay of machine-soil properties. In contrast to previous studies simulating worst field scenarios, this two-year field experiment investigated the effects of traffic-induced compaction involving moderate machine operational specifications (axle load, 3.16 Mg; mean ground contact pressure, 77.5 kPa) and lower field moisture contents (< field capacity) at the time of trafficking on soil physical properties, spatial root distribution, and corresponding maize growth and grain yield in sandy loam soil. Two compaction levels, i.e. two (C2) and six (C6) vehicle passes, were compared with a control (C0). Two maize (Zea mays L.) cultivars, i.e. ZD-958 and XY-335, were used. Results showed topsoil (< 30 cm) compaction with increases in bulk density (BD) and penetration resistance (PR) up to 16.42% and 127.76%, respectively, in the 10-20 cm soil layer in 2017. Field trafficking resulted in a shallower and stronger hardpan. An increased number of traffic passes (C6) aggravated the effects, and the carryover effect was found. Higher BD and PR impaired root proliferation in deeper layers of topsoil (10-30 cm) and promoted shallow horizontal root distribution. However, XY-335, compared with ZD-958, showed deeper root distribution under compaction. Compaction-induced reductions in root biomass and length densities were respectively up to 41% and 36% in 10-20 cm and 58% and 42% in the 20-30 cm soil layer. Consequent yield penalties (7.6%-15.5%) underscore the detriments of compaction, even only in topsoil. In crux, despite their low magnitude, the negative impacts of field trafficking under moderate machine-field conditions after just two years of annual trafficking foreground the challenge of soil compaction.